2015
DOI: 10.1016/j.cub.2015.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Coordination of Synaptogenesis and Neurotransmitter Signaling

Abstract: SUMMARY During nervous system development, postmitotic neurons face the challenge of generating and structurally organizing specific synapses with appropriate synaptic partners. An important unexplored question is whether the process of synaptogenesis is coordinated with the adoption of specific signaling properties of a neuron. Such signaling properties are defined by the neurotransmitter system that a neuron uses to communicate with postsynaptic partners, by the neurotransmitter receptor type used to receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 36 publications
5
81
0
Order By: Relevance
“…3B). However, consistent with a prior study (Kratsios et al, 2015), we found that overall muscle morphology is preserved -muscle arms extend normally to the nerve cord and the extent of muscle membrane contact with the nerve cord region is not appreciably altered (Fig. 3D).…”
Section: Unc-3 Transcriptional Regulation Coordinates Cholinergic Synsupporting
confidence: 92%
See 2 more Smart Citations
“…3B). However, consistent with a prior study (Kratsios et al, 2015), we found that overall muscle morphology is preserved -muscle arms extend normally to the nerve cord and the extent of muscle membrane contact with the nerve cord region is not appreciably altered (Fig. 3D).…”
Section: Unc-3 Transcriptional Regulation Coordinates Cholinergic Synsupporting
confidence: 92%
“…The remaining cholinergic transmission might reflect activity of cholinergic VC motor neurons, which do not require unc-3 for expression of cholinergic markers (Kratsios et al, 2012). Prior work identified a requirement for unc-3 in the clustering of postsynaptic ionotropic (nicotinic) acetylcholine receptors (iAChRs) in muscles (Kratsios et al, 2015). Confirming these observations, we find that the distribution of muscle iAChRs (visualized with ACR-16::GFP) is disrupted by mutation of unc-3 (Fig.…”
Section: Unc-3 Transcriptional Regulation Coordinates Cholinergic Synsupporting
confidence: 83%
See 1 more Smart Citation
“…We initially chose two different reporter transgenes for our genetic screens: ( a ) a reporter for unc-129 , a TGFβ-family member gene which is a direct target of UNC-3 (Kratsios et al, 2015) expressed in DA and DB classes of cholinergic VNC MNs (but not VA, VB and AS classes, where unc-3 actively promotes cholinergic identity yet is apparently not sufficient to induce unc-129 expression); ( b ) a reporter for unc-53 , a novel unc-3 -dependent gene encoding a cytoskeletal protein expressed in DA and AS, but not VA, DB or VB MN classes (Fig.4E,F). We mutagenized these reporter strains with ethyl methanesulfonate (EMS) and screened ~70,760 haploid genomes for expression defects of the unc-129 reporter and ~4500 haploid genomes for expression defects of the unc-53 reporter.…”
Section: Resultsmentioning
confidence: 99%
“…Each process innervates four cells in each quadrant and makes ϳ15-20 NMJs ( Fig. 4A; Zhao and Nonet, 2000; Kratsios et al, 2015). To determine whether rsu-1 ectopic clusters might be at ectopic synapses, we visualized SAB presynaptic boutons using the vesicle-associated membrane protein (VAMP) fused to GFP (Nonet, 1999).…”
Section: Rsu-1 Is Required In Muscle Cells To Prevent the Formation Omentioning
confidence: 99%